Effects of enzymes on the yield and quality of proteins extracted from microwave-vacuum stabilized rice bran - Baello, Genevieve D. (College of Home Economics, University of the Philippines Diliman, 2019)
This study aimed to determine the effects of enzymatic extraction on the functional properties of protein isolates from microwave vacuum (MV) stabilized rice bran. Specifically, the study: (a) determined the effects of MVon the proximate composition of rice bran and; (b) evaluated the effects of selected enzymes i.e. xylanase (X), Flavourzyme (F), cellulase (Ce) and their combinations i.e. xylanase-Flavourzyme (XF), xylanase-cellulase (XC), Flavourzyme-cellulase (FC), and xylanase-Flavourzyme-cellulase (XFC)on the extraction yield (g/g), emulsifying activity (EAI, m2/g) and stability (ESI, min), water absorption capacity (WAC, g/g), and oil absorption capacity (OAC, g/g) of rice bran proteins. Microwave stabilized rice branhad higher proximate composition compared to unstabilized rice bran. Extraction yield of enzyme-treated samples did not have significant (p>0.05) difference regardless of whether the samples were stabilized or unstabilized. There were also no significant differences (p>0.05) between the EAI, ESI, WAC, OAC of enzyme treated URB samples and control. For SRB samples, only the ESI and WAC had a significant (p>0.05) differences between the enzyme treatment-samplesand the control.The ESI of F-treated SRB samples were significantly (p>0.05) lesser than the control. This implies that the proteins extracted from URB have similar solubilities while the F coupled with stabilization treatments yielded less soluble proteins. The rank meansof enzyme treatments on SRB did not have a significant difference (p>0.05) with the control and this implies that the method should be improved.